Answer:
(2, 2 ) , (2, 1 ) , (- 1, 2 )
Explanation:
4x + y = 10 → (1)
4x + 4y = 16 → (2)
multiplying (1) by - 1 and adding to (2) will eliminate x
- 4x - y = - 10 → (3)
add (2) and (3) term by term to eliminate x
0 + 3y = 6
3y = 6 ( divide both sides by 3 )
y = 2
substitute y = 2 into either of the 2 equations and solve for x
substituting into (1)
4x + 2 = 10 ( subtract 2 from both sides )
4x = 8 ( divide both sides by 4 )
x = 2
solution is (2, 2 )
----------------------------------------------------------------------
3x + 2y = 8 → (1)
3x - y = 5 → (2)
multiplying (2) by 2 and adding to (1) will eliminate y
6x - 2y = 10 → (3)
add (1) and (3) term by term to eliminate y
9x + 0 = 18
9x = 18 ( divide both sides by 9 )
x = 2
substitute x = 2 into either of the 2 equations and solve for y
substituting into (1)
3(2) + 2y = 8
6 + 2y = 8 ( subtract 6 from both sides )
2y = 2 ( divide both sides by 2 )
y = 1
solution is (2, 1 )
----------------------------------------------------------------------------
- 2x + 3y = 8 → (1)
- 4x - 3y = - 2 → (2)
adding (1) and (2) term by term will eliminate y
- 6x + 0 = 6
- 6x = 6 ( divide both sides by - 6 )
x = - 1
substitute x = - 1 into either of the 2 equations and solve for y
substituting into (1)
- 2(- 1) + 3y = 8
2 + 3y = 8 ( subtract 2 from both sides )
3y = 6 ( divide both sides by 3 )
y = 2
solution is (- 1, 2 )